Fractured Therapists: The Consequences of Disintegrated Functioning in Faith and Practice - Scott, Seth L. (Journal of psychology and christianity, 2018)
With a renewed focus on strengthening professional identity in counseling, Christian counselors must improve the models and approaches for describing faith and spiritual development to incorporate critical elements of distinctive Christian worldviews into the process of establishing a professional identity. Without an ethical means for including components of faith and spirituality from the personal self into the professional self, Christian counselors become fractured and disintegrated practitioners, struggling to establish cohesion between the critical values of faith in their personal lives and the practical role of the Holy Spirit through their professional lives.